2021
DOI: 10.1371/journal.pone.0261367
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence and predictors of renal impairment in persons with HIV receiving protease-inhibitors in rural Tanzania

Abstract: Objective Ritonavir-boosted protease inhibitors (bPI) in people living with HIV (PLWH) have been associated with renal impairment. Limited data are available from rural sub-Saharan Africa. Methods Using data from the Kilombero and Ulanga Antiretroviral Cohort Study (KIULARCO) in rural Tanzania from 2005-01/2020, we assessed the prevalence of renal impairment (estimated glomerular filtration rate <60 mL/min/1.73m2) at the time of switch from first-line antiretroviral treatment (ART) to bPI-regimen and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…In this study, age was a strong predictor of reduced eGFR, a finding similar to other studies in SSA [ 10 , 11 , 12 ]. Studies have shown that chronic HIV infection accelerates aging and, even among ALHIV well controlled on ART, there is still an increased risk of age-related renal function loss [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, age was a strong predictor of reduced eGFR, a finding similar to other studies in SSA [ 10 , 11 , 12 ]. Studies have shown that chronic HIV infection accelerates aging and, even among ALHIV well controlled on ART, there is still an increased risk of age-related renal function loss [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…eGFR was estimated from serum creatinine using the 2021 CKD-EPI equation and was used as a continuous outcome in the regression analysis. The 2021 CKD-EPI formula is a race-free formulae that has been widely used to assess renal insufficiency among Africans in SSA [ 11 , 12 ]. Use of race-based CKD-EPI has been shown to overestimate eGFR if applied among African populations, consequently resulting in delayed initiation of nephrological care including dialysis initiation [ 31 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The long-term nature of the cohort—currently 17 years—and the large set of systematic clinical and laboratory data collected together with a large biobank make this cohort unique [ 2 , 5 ]. Based on its data and biobank important scientific manuscripts on treatment outcomes [ 3 , 6 , 7 ], mother to child transmission [ 8 , 9 , 10 ], comorbidities [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ], mortality [ 5 , 6 ] and other aspects were published and helped to adjust HIV service delivery to better meet patients’ needs.…”
Section: Kilombero and Ulanga Antiretroviral Cohort (Kiularco)mentioning
confidence: 99%